Optimalisasi Keterampilan 4C Siswa Melalui Pendampingan Karya Ilmiah di SMAN 1 Tumpang - Permana, Tutut Indria; Nuryady, Moh. Mirza (Jurnal SOLMA, 2025)
Background: Enhancing 4C skills (Critical Thinking, Creativity, Collaboration, and Communication) is one of the primary goals of 21st-century education. Schools play a crucial role as the main environment for developing these skills, fostered through a scientific writing mentorship program for students. This program was designed by a dedicated team to provide intensive guidance to 28 students of SMA Negeri 1 Tumpang in crafting and presenting high-quality scientific works. Through this process, students were trained to critically analyze problems, create innovative solutions, collaborate effectively within teams, and communicate their research findings. Methods: The approach employed consisted of interactive workshops, mentoring sessions, and continuous evaluation. Results: The evaluation included measuring 4C skills through tests, which revealed a high average score (93.21) with a low standard deviation (SD=5.808), indicating a homogeneous distribution of scores. The outcome of this community engagement activity was the establishment of a student extracurricular scientific writing group comprising 28 members with guidance from a teacher mentor. Conclusions: This program successfully enhanced students' academic skills while also preparing them to face future challenges with greater confidence and competence. Moreover, this learning approach serves as an inspirational model for developing 21st-century skills among the younger generation.